Assessing the role of resource based view (RBV) theory in determining micro-enterprises’ performances: A conceptual analysis - Abdul Aziz, Nor Aidil; Abu Bakar, Hatinah; Abdul Wahab, Mohd Hafez Al Amin (Journal of Islamic, Social, Economics and Development, 2026)
Micro-enterprises become the most numerous forms of business organization worldwide and play a critical role in employment generation and local economic development. Despite their numerical dominance, they frequently experience high mortality rates and persistent performance constraints. While the Resource-Based View (RBV) has been widely used to explain firm performance, its foundational assumptions—particularly those concerning firm boundaries, resource ownership, and strategic stability—are not fully aligned with the structural realities of micro-enterprises. This conceptual paper assesses the applicability of RBV in explaining micro-enterprise performance and proposes an extension of the theory. Building on recent developments in RBV and entrepreneurship research, the paper develops an integrated conceptual framework comprising four interrelated components: resource categories (tangible, intangible, and hybrid individual–firm resources), entrepreneurial capabilities, resource orchestration processes, and multidimensional performance outcomes. The framework emphasizes the central role of the owner-manager, reconceptualizes resources as hybrid and context dependent, and incorporates dynamic adaptation through resource orchestration. It further recognizes contextual embeddedness as a boundary condition shaping resource value and utilization. By extending RBV to account for informality, managerial agency, and dynamic recombination, the study enhances its theoretical relevance for micro-enterprise contexts. The framework provides a structured foundation for future empirical research and offers policy and practical insights for strengthening micro-enterprise performance in resource-constrained environments.